2010
DOI: 10.1149/1.3485255
|View full text |Cite
|
Sign up to set email alerts
|

ALD TaN from PDMAT in TSV Architectures

Abstract: In this study, we report the TaN ALD film growth from PDMAT, in Through-Silicon Vias with NH3 as nitrogen precursor and H2 as reducing agent. We report deposits on planar and patterned substrates with high aspect ratios (5 to 20). As a reference, TaN was deposited from PDMAT and NH3 only, and the influence of H2 injections as reducing agent is reported. H2 was introduced in two manners: either during the PDMAT pulse or during the NH3 pulse. The samples obtained when H2 is introduced during the PDMAT pulse show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…PDMAT was supplied in a standard stainless steel bubbler provided by Air Products heated up at a temperature of 343 K. PDMAT vapor was carried into the reactor by high purity argon (H 2 O < 0.5 ppm, O 2 < 0.1 ppm, C n H m < 0.1 ppm). The ALD experimental conditions (pulse time, flow rate, temperature) have been optimized, using in situ microgravimetry study (19). The deposition was investigated in the temperature range of 370-525 K. It was confirmed that films deposited from PDMAT and NH 3 contain a high level of oxygen (above 10%) and a lower level of "free" carbon impurities as already reported (5,6,9,(19)(20)(21).…”
Section: Methodssupporting
confidence: 55%
See 4 more Smart Citations
“…PDMAT was supplied in a standard stainless steel bubbler provided by Air Products heated up at a temperature of 343 K. PDMAT vapor was carried into the reactor by high purity argon (H 2 O < 0.5 ppm, O 2 < 0.1 ppm, C n H m < 0.1 ppm). The ALD experimental conditions (pulse time, flow rate, temperature) have been optimized, using in situ microgravimetry study (19). The deposition was investigated in the temperature range of 370-525 K. It was confirmed that films deposited from PDMAT and NH 3 contain a high level of oxygen (above 10%) and a lower level of "free" carbon impurities as already reported (5,6,9,(19)(20)(21).…”
Section: Methodssupporting
confidence: 55%
“…To evaluate ECS Transactions, 33 (2) 321-332 (2010) the use of an additional reducing agent, H 2 gaseous flow was added either during the PDMAT pulse, or during the NH 3 pulse. It was found that H 2 addition in the PDMAT pulse improves the films quality in terms of oxygen contamination while oxygen contamination increases when H 2 is introduced during the NH 3 pulse (19). In both cases, the ALD regime is degraded (19).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations